Association of echocardiographic measures of left ventricular diastolic dysfunction and hypertrophy with presence of coronary microvascular dysfunction. (April 2020) - Dykun, Iryna; Kärner, Luisa; Mahmoud, Ihab; Hendricks, Stefanie; Totzeck, Matthias; Al-Rashid, Fadi; Rassaf, Tienush; Mahabadi, Amir A.
Abstract: Background: Coronary microvascular dysfunction (CMD) is a common disorder, leading to symptoms similar to obstructive coronary artery disease. We aimed to determine whether measures of left ventricular (LV) diastolic function and hypertrophy may predict presence of CMD. Methods: We retrospectively included patients undergoing diagnostic coronary angiography and transthoracic echocardiography, excluding patients with obstructive coronary artery disease, previous revascularization therapy, moderate or severe mitral valve disease, or atrial fibrillation. The following markers of LV diastolic function and hypertrophy were assessed: E- and A-wave velocity, E-wave deceleration time, E/A- and E/E′-ratio, left atrial area, left LV mass index, LV ejection time (LVET) and mitral valve closure to opening time. Logistic regression analysis was used to determine the association of echocardiographic parameters with presence of CMD. Results: From 378 patients (mean age ± SD 59.7 ± 13.6 years, 45.6% male) included, the majority had CMD (n = 293, 77.5%). Patients with CMD were older (60.5 ± 13.4 years vs. 56.9 ± 14.3 years, p = 0.03), were less frequent male (42.3% vs. 57.0%, p = 0.02), and had higher systolic blood pressure (137.9 ± 25.7 mmHg vs. 124.7 ± 25.6 mmHg, p < 0.0001). LVET was significantly associated with CMD (1.42 [1.02–1.96], p = 0.04), while a non-statistically significant link was observed for A-wave velocity and E/E′-ratio (1.39 [0.96–2.00], p = 0.08 and 1.40 [0.92–2.13], p = 0.1, respectively). For all other echocardiography-derived measures, odds ratio for the association with CMD was <1.3 per each SD increase. Conclusions: In this cross-sectional single-center cohort study, CMD was a frequent finding in patients undergoing coronary angiography for suspected obstructive coronary artery disease. LVET from transthoracic echocardiography is associated with the presence of CMD.